Modern labor economics: Theory and public policy - Ehrenberg, Ronald G.; Smith, Robert S.; Hallock, Kevin F. (New York Routledge, 2026)
odern Labor Economics: Theory and Public Policy, now in its fifteenth edition, continues to be the leading text for one-semester courses in labor economics at the undergraduate and graduate levels. It offers a thorough overview of the modern theory of labor market behavior and reveals how this theory is used to analyze public policy. Designed for students who may not have extensive backgrounds in economics, the text balances theoretical coverage with examples of practical policy applications that allow students to see concepts in action.